Synthesis, photophysics and computational study of a neutral n- associated supramolecular systems - [2] rotaxane & its components- - Kumara, M.N.C. (My University, 2009)
The first part of this project involved the non-conventional approach to build a large molecularsystem called [2]rotaxane. The methodology exploited the use of non-covalent interactionsto buildthe supramolecularassembly, [2]rotaxane. In the second part of this project, fluorescence studies on metal ions (Na+, K+and Cs1 boundlargearomaticcrownether,bis-l,5-(naptha)-38-crown-lOwerealsoinvestigated. In the final part, HyperChem computational package was used to search the conformationsand stabilitiesof the crown ether, bis-l,5-(naptha)-38-crown-1O,in gas phase and "host-guest"interactionsof this crown ether (host) were studied with pyromellitic diimide (guest) usingmolecularmechanicsM~ method.